Analysis of the In Vitro Transcriptional Response of Human Pharyngeal Epithelial Cells to Adherent Streptococcus pneumoniae: Evidence for a Distinct Response to Encapsulated Strains - Bootsma, Hester J. (American Society for Microbiology (ASM), 2007)
Infection of the human host by Streptococcus pneumoniae begins with colonization of the nasopharynx, which is mediated by the adherence of bacteria to the respiratory epithelium. Several studies have indicated an important role for the pneumococcal capsule in this process. Here, we used microarrays to characterize the in vitro transcriptional response of human pharyngeal epithelial Detroit 562 cells to the adherence of serotype 2 encapsulated strain D39, serotype 19F encapsulated strain G54, serotype 4 encapsulated strain TIGR4, and their nonencapsulated derivatives (Δcps). In total, 322 genes were found to be upregulated in response to adherent pneumococci. Twenty-two genes were commonly induced, including those encoding several cytokines (e.g., interleukin 1β [IL-1β] and IL-6), chemokines (e.g., IL-8 and CXCL1/2), and transcriptional regulators (e.g., FOS), consistent with an innate immune response mediated by Toll-like receptor signaling. Interestingly, 85% of genes were induced specifically by one or more encapsulated strains, suggestive of a capsule-dependent response. Importantly, purified capsular polysaccharides alone had no effect. Over a third of these loci encoded products predicted to be involved in transcriptional regulation and signal transduction, in particular mitogen-activated protein kinase signaling pathways. Real-time PCR of a subset of 10 genes confirmed the microarray data and showed a time-dependent upregulation of, especially, innate immunity genes. The downregulation of epithelial genes was most pronounced upon adherence of D39Δcps, as 68% of the 161 genes identified were repressed only by this nonencapsulated strain. In conclusion, we identified a subset of host genes specifically induced by encapsulated strains during in vitro adherence and have demonstrated the complexity of interactions occurring during the initial stages of pneumococcal infection.